Detergent waste treatment through the modification of biofilter reactors - Suprijandani Suprijandani; Suryono Hadi; Narwati Narwati (International Journal of Public Health Science (IJPHS), 2021)
The use of detergent in households is practiced by almost all people. These conditions make the quality of the environment, especially water bodies, more disturbed when the detergent waste disposal without prior processing. Hazard by detergent can interfere with human health such as digestive system disorders, skin irritation, and even one of the causes of cancer. The aimed of this research was to design a modified biofilter reactor to reduce levels of detergent and other organic substances in domestic wastewater. This research was a pre-experimental design research with designs used is pre-test, treatment, and post-test. The research media used were bioball because bioball has more space on its surface for bacterial growth that will form bacterial phylum, while activated carbon serves to increase efficiency in reducing levels of organic matter and to reduce the concentration of surfactants dissolved. The process is more effective if given a treatment with a process of coagulation, flocculation, and sedimentation. The results showed a decrease in detergent content from 14.56 mg/L to 0.86 mg/L (94.1%). These results indicate that the Bio Filter reactor was effective in reducing detergent levels to meet the detergent waste standard requirements based on East Java Governor Regulation No. 72/2013.